2020
DOI: 10.3390/nu12082310
|View full text |Cite
|
Sign up to set email alerts
|

Association between Biomarkers of Cardiovascular Diseases and the Blood Concentration of Carotenoids among the General Population without Apparent Illness

Abstract: Several studies have demonstrated that carotenoid-rich vegetables are useful against cardiovascular diseases (CVDs). However, it is still unclear when a healthy population should start eating these vegetables to prevent CVDs. In this study, we evaluated the role of carotenoids in CVD markers in healthy subjects using age-stratified analysis. We selected 1350 subjects with no history of apparent illness who were undergoing health examinations. We then evaluated the relationship between the serum concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…As described in our previous report [ 8 ], the mean value of each measurement was stratified by sex (male and female) and compared using Student’s t -test. It was also stratified by age category (young, 20–39 years; middle-aged, 40–59 years; old ≥60 years) and compared using one-way ANOVA (post hoc: Bonferroni).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As described in our previous report [ 8 ], the mean value of each measurement was stratified by sex (male and female) and compared using Student’s t -test. It was also stratified by age category (young, 20–39 years; middle-aged, 40–59 years; old ≥60 years) and compared using one-way ANOVA (post hoc: Bonferroni).…”
Section: Methodsmentioning
confidence: 99%
“…It was also stratified by age category (young, 20–39 years; middle-aged, 40–59 years; old ≥60 years) and compared using one-way ANOVA (post hoc: Bonferroni). Because previous studies have shown that carotenoid concentrations do not follow normality [ 8 ], Mann–Whitney U test and Kruskal–Wallis test (post hoc: Bonferroni) were used for the carotenoids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Korea National Health and Nutrition Examination Survey, it was observed that the proportion of men affected by diabetes was 60.1%, although no correlation of its development with the consumption of carotenoids was shown [ 66 ]. Nevertheless, in another study, it was observed that Japanese men and women who consumed higher quantities of plant sources of carotenoids presented higher concentrations of serum β-carotene and lower insulin resistance, indicating a possible protective role of this antioxidant for β-pancreatic cells [ 68 ].…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%